BVRIPHOTOMETRY OF THE BRIGHTEST STARS IN THE MAGELLANIC CLOUDS - MENDOZA, EUGENIO (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1969)
We have made photometric observations in the BVRI system of 100 objects that belong to the Magellanic Clouds. The observational data indicate at least two remarkable differences between some of the Magellanic Cloud objects and the supergiant stars in the
BOL OBS TONAN TACUB
Keywords: BVRI, PHOTOMETRY, BRIGHTEST STARS, MAGELLANIC, CLOUDS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS